INFLUENCE OF PREGNANT WOMEN HEALTH CARE ON INFANT MORTALITY RATE IN INDONESIA - Cindy Eka Pratiwi; Erika Yulinda; Arum Cahyaning Utami; Fahrudi Akhwan Ikhsan; Fahmi Arif Kurnianto (DEPARTMENT OF GEOGRAPHY EDUCATION, UNIVERSITY OF JEMBER, 2019)
Health development is an inseparable part of national development that aims to increase awareness, willingness and ability to live healthy for every person to realize the highest degree of public health. Health has a dual role in national development, therefore health is one of the goals of development while on the other hand health is the basic capital in national development. Health development efforts are reflected in health programs through promotive, preventive, and rehabilitative. Health development is one of the efforts to improve community health status. Achieving optimal health status is not only the responsibility of health personnel, but other sectors such as education, economy, social and government sectors also have a significant role in efforts to increase health insurance in Indonesia. Using secondary data sourced from BPS 2013 and DG of Disease Prevention and Control, Ministry of Health 2017. Data analysis used is product moment correlation to know strength of relation between 2 variables. Based on the results of the calculation of the data obtained a correlation of 0.608085 which indicates that the data meets the criteria of a strong correlation relationship so that service delivery facilities at the puskesmas that provide delivery services are in accordance with the standards in Indonesia, so that service delivery facilities in Indonesia show criteria that are strongly correlated. increasing deficiencies which have been a health problem in Indonesia. Key words : Health devepment, facilities, public health References: IFA, Hoday et al. ANALISIS SOSIAL EKONOMI TERHADAP TINGKAT KESEJAHTERAAN MASYARAKAT TENGGER GUNUNG BROMO.MAJALAH PEMBELAJARAN GEOGRAFI, [S.l.], v. 2, n. 1, p. 169-175, june 2019. ISSN 2622-125X. Available at: <https://jurnal.unej.ac.id/index.php/PGEO/article/view/12305>. Date accessed: 12 aug. 2019. PAHLEVY, Fahrizal Novan; APRIYANTO, Bejo; ASTUTIK, Sri. KARAKTERISTIK SOSIAL EKONOMI MASYARAKAT DAERAH WISATA BROMO SEBAGAI PENGEMBANGAN KESEJAHTERAAN HIDUP. MAJALAH PEMBELAJARAN GEOGRAFI, [S.l.], v. 2, n. 1, p. 172-189, june 2019. ISSN 2622-125X. Available at: <https://jurnal.unej.ac.id/index.php/PGEO/article/view/12177>. Date accessed: 12 aug. 2019. HARYANTI, Titik Umaiyah. PERANAN PANTAI DALAM KONDISI SOSIAL EKONOMI MASYARAKAT DISEKITAR PANTAI BENTAR KABUPATEN PROBOLINGGO JAWA TIMUR.MAJALAH PEMBELAJARAN GEOGRAFI, [S.l.], v. 1, n. 1, p. 12-16, aug. 2018. ISSN 2622-125X. Available at: <https://jurnal.unej.ac.id/index.php/PGEO/article/view/8336>. Date accessed: 12 aug. 2019. UMAM, Muhammad Fikri; ALHIDAYAH, Yazid; FAUZIYAH, Rita. ANALISIS MATERIAL ENDAPAN VULKAN GUNUNG SEMERU KABUPATEN LUMAJANG. MAJALAH PEMBELAJARAN GEOGRAFI, [S.l.], v. 2, n. 1, p. 92-98, june 2019. ISSN 2622-125X. Available at: <https://jurnal.unej.ac.id/index.php/PGEO/article/view/11522>. Date accessed: 12 aug. 2019. SETYAWAN, Muhammad Alif; APRIYANTO, Bejo; ASTUTIK, Sri. ANALISIS KARAKTERISTIK ENDAPAN MARINE DAN PENGARUHNYA BAGI SEKTOR PERTANIAN DAN PERAIRAN DI PESISIR SELATAN PANTAI PANCER KECAMATAN PUGER KABUPATEN JEMBER JAWA TIMUR. MAJALAH PEMBELAJARAN GEOGRAFI, [S.l.], v. 2, n. 1, p. 141-154, june 2019. ISSN 2622-125X. Available at: <https://jurnal.unej.ac.id/index.php/PGEO/article/view/11760>. Date accessed: 12 aug. 2019. KURNIANTO, Fahmi Arif et al. THE ENVIRONMENT ANALYSIS OF POPULATION GROWTH, UNEMPLOYMENT, AND POVERTY LEVEL IN MAESAN DISTRICT BONDOWOSO REGENCY. Geosfera Indonesia, [S.l.], v. 3, n. 2, p. 113-121, aug. 2018. ISSN 2614-8528. Available at: <https://jurnal.unej.ac.id/index.php/GEOSI/article/view/8439>. Date accessed: 12 aug. 2019. doi: https://doi.org/10.19184/geosi.v3i2.8439. SARI, Eva Kurnia; PRAMESTY, Dinda Ayu. THE EFFECT OF VEHICLES INTENSITY IN SUMBERSARI JEMBER REGENCY. Geosfera Indonesia, [S.l.], v. 3, n. 3, p. 50-58, jan. 2019. ISSN 2614-8528. Available at: <https://jurnal.unej.ac.id/index.php/GEOSI/article/view/9300>. Date accessed: 12 aug. 2019. doi: https://doi.org/10.19184/geosi.v3i3.9300. LESTARI, Dwi et al. ANALISIS FENOMENA GEOGRAFI FISIK PADA PENGUKURAN PROSES DAN HASIL PROSES BENTANG ALAM JAWA TENGAH. MAJALAH PEMBELAJARAN GEOGRAFI, [S.l.], v. 2, n. 1, p. 110-118, june 2019. ISSN 2622-125X. Available at: <https://jurnal.unej.ac.id/index.php/PGEO/article/view/11626>. Date accessed: 12 aug. 2019. ZAHROH, Faidatuz; ELFIANI, Vira; H, Arya Bagas. ASPEK SOSIAL DAERAH KARST PUGER DALAM PRESPEKTIF EKONOMI. MAJALAH PEMBELAJARAN GEOGRAFI, [S.l.], v. 2, n. 1, p. 155-160, june 2019. ISSN 2622-125X. Available at: <https://jurnal.unej.ac.id/index.php/PGEO/article/view/11780>. Date accessed: 12 aug. 2019. NURIYANTO, Muhammad Zaid; FIRMANSYAH, Fahrul Agil; PRASETYONO, Ica. ANALISIS PERUBAHAN BENTANG GEOMORFOLOGI PANTAI BENTAR KABUPATEN PROBOLINGGO.MAJALAH PEMBELAJARAN GEOGRAFI, [S.l.], v. 2, n. 1, p. 99-109, june 2019. ISSN 2622-125X. Available at: <https://jurnal.unej.ac.id/index.php/PGEO/article/view/11523>. Date accessed: 12 aug. 2019.